Characterization of functional SSR markers in Prosopis alba and their transferability across Prosopis species - Pomponio, Maria Florencia; Acuña, Cintia Vanesa; Petreath, Vivien; Lopez Lauenstein, Diego; Marcucci Poltri, Susana Noemi; Torales, Susana Leonor (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (España), 2022)
Aim of study: The aim of the study was to characterize functional microsatellite markers in Prosopis alba and examine the transferability to species from the Prosopis genus. Area of the study: samples were obtained from natural populations of Argentina. Material and Methods: Eleven SSR functional markers related to stress and metabolism were amplified in a sample of 152 genotypes from P. alba, P. denudans, P. hassleri P. chilensis, P. flexuosa, and interspecific hybrids. Main results: In P. alba, the PIC average value was 0.36; and 6 out of the 11 primers showed high values of polymorphism ranging from 0.40 to 0.71. The cross-species transferability was high with high percentages of polymorphic loci. Research highlights: The SSR markers developed in P.alba were easily transferred to other Prosopis species which did not have functional markers.